2012
DOI: 10.3747/pdi.2010.00109
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Peripheral Arterial Disease Predicts Loss of Residual Renal Function in Incident CAPD Patients

Abstract: ♦ Background: Accelerated cardiovascular disease (CVD), including peripheral arterial disease (PAD), is very common in patients with end-stage renal disease. Residual renal function (RRF) is a strong predictor of patient survival that is suggested to be linked to the degree of CVD. However, the relationship between PAD and decline in RRF has not previously been measured. ♦ Methods: We studied incident continuous ambulatory peritoneal dialysis patients from Peking University Third Hospital. An ankle brachial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…A reduced ankle–brachial index reflects peripheral arterial disease, and some studies demonstrated that this atherosclerotic disease marker predicted accelerated renal function decline, in general population,42 and also in peritoneal dialysis patients 43…”
Section: Discussionmentioning
confidence: 99%
“…A reduced ankle–brachial index reflects peripheral arterial disease, and some studies demonstrated that this atherosclerotic disease marker predicted accelerated renal function decline, in general population,42 and also in peritoneal dialysis patients 43…”
Section: Discussionmentioning
confidence: 99%
“…Since data in table 3 suggested that the patients treated with fewer initial HD frequency had less incidence of RKF loss than patients treated with regular thrice-weekly HD, a Receiver Operating Characteristic (ROC) analysis was performed to decide the cut-off value of a 50% decline rate of GFR in a year for predicting whether the patient has lost RKF or not, as previously reported [35,36]. We found the best cut-off value was 0.044 (4.4%) with a specificity of 75% and a sensitivity of 64% (AUC = 0.65, p < 0.05) (see online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…This is a hypothetical cutoff for RRF decline. Some studies have used this as a criterion to indicate a significant decline in RRF [16,17]. Anuria was defined as <100 mL/day of urine volume.…”
Section: Methodsmentioning
confidence: 99%
“…The weekly Kt/V urea was calculated on the basis of 24-h urine and dialysate as follows: weekly Kt/V urea = 7 × {[24-h urine urea nitrogen content (mg/dL) × 24-h urine volume (L)] + [24-h dialysate urea nitrogen content (mg/dL) × 24-h drain volume (L)]}/[distribution volume of urea (L) × serum urea nitrogen (mg/dL)] [15]. The distribution volume of urea was calculated with V , estimated from a previous study [16]. Inadequate dialysis was defined as a weekly Kt/V urea value of < 1.7 in the K/DOQI guideline [5].…”
Section: Methodsmentioning
confidence: 99%